Nurses' perspectives of the impact of the older person on nursing resources in the emergency department and their profile: A mixed methods study. Issue 4 (October 2015) - Gallagher, Robyn; Gallagher, Patrick; Roche, Michael; Fry, Margaret; Chenoweth, Lynn; Stein-Parbury, Jane
Highlights ED nurses associate greater workloads with older patients who represent frequently in a short timeframe (cluster presenters). Cluster presenters are perceived to require more nursing resources due to multiple chronic and/or comorbid conditions. Cluster presenters require a full assessment at each presentation and are usually admitted to the hospital.